(untitled) (Revista Brasileira de Ciências do Envelhecimento Humano, 2014)
Alzheimer’s Disease is characterized by a progressive loss of cognitive and behavioral functions, also caused by changes to the neuroendocrine system and eating behaviors, and can lead to patient malnutrition and result in a nutritional imbalance with consequent malnutrition, affecting the overall health condition in patients, causing organic complications and influences in the evolution of dementia. The study objective present some information relating to the main factors involved in weight loss in AD patients reported in previous studies. As method use non-systematic review of the literature in the period 1988-2014, with search conducted in MEDLINE, LILACS and SciELO electronic library. Results 58 scientific articles reviewed and subdivided in categories for discussion, like cognitive losses, psychological symptoms, dysphagia and others. Conclude that unfulfilled nutritional needs associated with increased energy demands and various alterations can lead to a rapid, undesirable, and sharp decline in nutritional status in patients with AD.